Validation of the simplified modified Rankin scale for stroke trials: Experience from the ENCHANTED alteplase-dose arm - Xiaoying Chen; Jingwei Li; Craig S Anderson; Richard I Lindley; Maree L Hackett; Thompson Robinson; Pablo M Lavados; Xia Wang; Hisatomi Arima; John Chalmers; Candice Delcourt (My University, 2020)
Background and aims The structured, simplified modified Rankin scale questionnaire (smRSq) may increase reliability over the interrogative approach to scoring the modified Rankin scale (mRS) in acute stroke research and practice. During the conduct of the alteplase-dose arm of the international ENhanced Control of Hypertension ANd Thrombolysis StrokE stuDy (ENCHANTED), we had an opportunity to compare each of these approaches to outcome measurement. Methods Baseline demographic data were recorded together with the National Institutes of Health Stroke Scale (NIHSS). Follow-up measures obtained at 90 days included mRS, smRSq, and the 5-Dimension European Quality of life scale (EQ-5D). Agreements between smRSq and mRS were assessed with the Kappa statistic. Multiple logistic regression was used to identify baseline predictors of Day 90 smRSq and mRS scores. Treatment effects, based on Day 90 smRSq/mRS scores, were tested in logistic and ordinal logistic regression models. Results SmRSq and mRS scores had good agreement (weighted Kappa 0.79, 95% confidence interval (CI) 0.78–0.81), while variables of age, atrial fibrillation, diabetes mellitus, pre-morbid mRS (1 vs. 0), baseline NIHSS scores, and imaging signs of cerebral ischemia, similarly predicted their scores. Odds ratios for death or disability, and ordinal shift, 90-day mRS scores using smRSq were 1.05 (95% CI 0.91–1.20; one-sided P = 0.23 for non-inferiority) and 0.98 (95% CI 0.87–1.11; P = 0.02 for non-inferiority), similar to those using mRS. Conclusions This study demonstrates the utility of the smRSq in a large, ethnically diverse clinical trial population. Scoring of the smRSq shows adequate agreement with the standard mRS, thus confirming it is a reliable, valid, and useful alternative measure of functional status after acute ischemic stroke. Clinical Trial registration URL: http://www.clinicaltrials.gov . Unique identifier: NCT01422616.
Keywords: simplified modified rankin scale questionnaire; modified rankin scale; ischemic stroke; clinical trial; health outcome; brain ischemia; humans; quality of life; reproducibility of results; stroke; tissue plasminogen activator; treatment outcome; alteplase; tissue plasminogen activator; adult; aged; article; atrial fibrillation; brain ischemia; cerebrovascular accident; clinical effectiveness; controlled study; demography; diabetes mellitus; disability; dose response; drug dose comparison; drug efficacy; european quality of life 5 dimensions questionnaire; female; follow up; functional status; human; major clinical study; male; multicenter study; national institutes of health stroke scale; priority journal; quality of life; randomized controlled trial; rankin scale; treatment outcome; treatment planning; validation study; brain ischemia; reproducibility